Information Access Capability of Goat Farmers in Purworejo Indonesia - Guntoro, Budi (International Information Institute, 2016)
This study analyzed the type of knowledge information needed by goat farmer and recovered the level of farmers competence in doing their business, analyzed the cannal used to disseminate the knowledge information, and described participation in accessing market and factors influence to their participation. This research used survey method. The result showed that there was significant relationship between access of knowledge level and level of innovation. Information type that relevan significantly was marketing and reproduction domains. The result also showed that experienced learning was the key for farmers in doing their animal busniess. farmer participation in market access used indicator for knowing price of market, selling animal directly to market, and selling goat independently at any time.